ASPLENIUM TENERUM VAR. PALLIDUM IS THE CORRECT NAME FOR A. THUNBERGII VAR. BELANGERI (ASPLENIACEAE) - VELDKAMP, J. F.; WARDANI, WITA (REINWARDTIA, 2015)
VELDKAMP J. F. & WARDANI, W. 2015. Asplenium tenerum var. pallidum is the correct name for A. thunbergii var. belangeri (Aspleniaceae). Reinwardtia 14(2): 303 - 306. - Asplenium tenerum G. Forst. var. pallidum (Blume) Veldk. & Wardani, comb. nov. (Aspleniaceae), is the correct name for what usually is known as A. thunbergii Kunze var. belangeri (Bory) Kunze. Types are designated.